From Preservation to Collaboration: A Bibliometric Study of the Transformation of Library Digital Archives - Fairus Faqih; Hendro Margono (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2026)
Background: Digitization has reshaped management across library science. Over the past decade, libraries have adopted digital co-creation, AI, and automation to enhance access and services. Yet the shift from preservation-oriented to collaboration-centered approaches in digital archives remains underexplored.Objective: To map the thematic evolution of digital innovation in library management (2011-2025) and assess shifts from preservation frameworks toward collaborative, participatory, and AI-assisted approaches.Methods: A bibliometric analysis of 263 Scopus-indexed articles (2011-2025) was conducted using the Bibliometrix R package and Biblioshiny. Performance analysis, science mapping, and thematic evolution were applied, comparing two periods (2011-2021; 2022-2025).Results: Scholarly output increased notably after 2019. Three core clusters were identified: digital technologies, digital libraries, and humanities. Recent work highlights collaboration, blockchain-based management, AI-driven curation, and participatory archiving. Emerging topics include language processing, digital library services, and large language models.Conclusion: Digital innovation in library management has moved from a preservation-centric to a collaboration-oriented paradigm. The study clarifies this transformation and informs the design of tools, policies, and collaborative frameworks. Libraries should strengthen competencies in participatory digital preservation and AI integration to support future-ready information management.